IDENTIFIKASI RISIKO PELAKSANAAN PEMBANGUNAN PROYEK GEDUNG HIGHRISE BUILDING DI HOTEL GRAND DAFAM SIGNATURE YOGYAKARTA - M.Hendra Aulia Rahman; Hanie Teki Tjendani (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2022)
This research was conducted to the identifying dominant risks and risk allocation Grand Dafam Signature Hotel Yogyakarta Building Project. Using quantitative research methods. The research sample amounted to 18 people, including expert staff from the implementing contractor and supervisory consultant. Data collection is based on the distribution of primary data, namely questionnaires and interviews with selected respondents and secondary data, research literature and previous similar project data. Based on the output of the data processing stages, there is a dominant risk. There were 27 selected risk variables, from the analysis results obtained 6 dominant risk variables, namely the increase in material prices, material damage or loss, occupational health and safety (K3) at the project location due to safety regulations that were not implemented in the field, design changes, schedule changes. execution of work and late payment in the contract, based on the distribution of the results of the risk allocation assessment, 17 (seventeen) risks are allocated to the contractor, 3 (three) risks are allocated to the owner, 7 (seven) risks are allocated jointly (shared), with a percentage distribution of risk allocation to the contractor 63%, the owner 11% and allocated jointly (shared) of 26%.